2019
DOI: 10.1007/s11051-019-4544-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by surroundings of the antibacterial efficiency of silver in water environments

Abstract: Silver is a usual antibacterial agent acting in water solutions. However, quantitative data fail to anticipate the silver availability for interactions with bacterial cells and the resulting fluctuations of the inhibitory and bactericidal concentrations according to silver amount and chemical composition of the liquid environment. We investigated whether and how three different biological media modify silver ions (Ag + ) and nanoparticles (AgNPs), and alter their antibacterial performances against Escherichia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In particular, the bacterial strain, culture medium and temperature are parameters known to affect bacterial sensitivity to antibacterial agents. 62,63 Thus, reported studies 64,65 and results obtained by our group using M63G culture medium 66 have shown that the interactions of Ag + ions with compounds in different media reduce the amount of Ag + available for antibacterial action. Despite these interactions, however, the results reported here demonstrate that Ag + ions were released from the ZnPOs/Ag-750 material in sufficient amounts to affect both bacterial colonization and proliferation and therefore to endow it with antibacterial properties.…”
Section: Resultsmentioning
confidence: 95%
“…In particular, the bacterial strain, culture medium and temperature are parameters known to affect bacterial sensitivity to antibacterial agents. 62,63 Thus, reported studies 64,65 and results obtained by our group using M63G culture medium 66 have shown that the interactions of Ag + ions with compounds in different media reduce the amount of Ag + available for antibacterial action. Despite these interactions, however, the results reported here demonstrate that Ag + ions were released from the ZnPOs/Ag-750 material in sufficient amounts to affect both bacterial colonization and proliferation and therefore to endow it with antibacterial properties.…”
Section: Resultsmentioning
confidence: 95%
“…This leads to the leakage of cellular components through the pores of the perforated cellular membrane. Once inside, the ions promote reactive oxygen species (ROS) generation, deactivate proteins, and block DNA replication [ 21 ]. Silver nanoparticles (AgNPs) have the added benefit of being ionic silver vessels, combining the latter’s antimicrobial properties with their own characteristics [ 16 ].…”
Section: Introductionmentioning
confidence: 99%